Produksi Dalam Ekonomi Islam Perspektif Maqashid Syariah - Trisno Wardy Putra; Rika Dwi Ayu Parmitasari; Idris Parakkasi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to analyze production activities in the perspective of Islamic economics with the maqashid sharia approach. The method used is descriptive qualitative through literature studies that utilize secondary data from various literature sources. The results of the study indicate that production in Islam is not only oriented towards material profit, but must also fulfill the five main objectives of maqashid sharia: maintaining religion, soul, mind, descendants, and property. Production must avoid goods that are forbidden and dangerous, and pay attention to sustainability and social responsibility. In addition, maqashid sharia emphasizes the importance of maintaining five main aspects: religion, soul, mind, descendants, and property. This study also identifies two important prohibitions in production, namely the prohibition of producing forbidden goods and dangerous goods.Keywords: Production, Islamic Economics, Maqashid Sharia